Detecting Patient Safety Errors by Characterizing Incidents Reported by Medical Imaging Staff - Tarkiainen, Tarja; Sneck, Sami; Haapea, Marianne; Turpeinen, Miia; Niinimäki, Jaakko (Frontiers in Public Health, 2022)
The objectives of the study were to characterize events related to patient safety reported by medical imaging personnel in Finland in 2007–2017, the number and quality of reported injuries, the risk assessment, and the planned improvement of operations. The information was collected from a healthcare patient safety incident register system. The data contained information on the nature of the patient safety errors, harms and near-misses in medical imaging, the factors that lead to the events, the consequences for the patient, the level of risks, and future measures. The number of patient safety incident reports included in the study was 7287. Of the incident reports, 75% concerned injuries to patients and 25% were near-misses. The most common consequence of adverse events and near-misses were minor harm (37.2%) related to contrast agent, or no harm (27.9%) related to equipment malfunction. Supervisors estimated the risks as low (47.7%) e.g. data management, insignificant (35%) e.g. verbal communication or moderate (15.7%) e.g. the use of contrast agent. The most common suggestion for learning from the incident was discussing it with the staff (58.1%), improving operations (5.7%) and submitting it to a higher authority (5.4%). Improving patient safety requires timely, accurate and clear reporting of various patient safety incidents. Based on incident reports, supervisors can provide feedback to staff, develop plans to prevent accidents, and monitor the impact of measures taken. Information on the development of occupational safety should be disseminated to all healthcare professionals so that the same mistakes are not repeated.